Registration Nazhir To The Minister Of Religion Of Indonesia: A Perspective Review Of The Rules Of Islamic Law - Luthfi, Muhammad; Fajrin, Yaris Adhial (Universitas Negeri Gorontalo, 2023)
The birth of the Waqf Law and the Waqf Implementation Regulations brought a new policy direction regarding the regulation of nazhir. Nazhir as an institution that plays a role in the process of productivity of waqf assets is required to be professional in carrying out their duties, therefore a new regulation is formed regarding the nazhir registered with the Ministry of Religion. Regulations for the implementation of waqf in several articles state the obligation to register nazhir, but the rules for these obligations are not accompanied by sanctions rules that allow punishment for those who do not implement these rules. This study discusses the policy of registering nazhir before and after the issuance of the Waqf Law and the policy of registering nazhir to the Minister of Religion from the perspective of the rules of Islamic law. This research is normative research, with a prescriptive discussion. The results of this study stated that the rules for registering nazhir before the issuance of the Waqf Law are contained in the Land Waqf Regulation and Presidential Instruction Number 1 of 1991, while the rules for registering nazhir after the birth of the Waqf Law are contained in Article 14 (1) of the Waqf Law. In terms of Islamic law, nazhir's registration rules to the Minister of Religious Affairs meet the elements of ijtihad through mashlahah mursalah and amr studies in ushuliyyah rules.